Cell type mapping of mild malformations of cortical development with oligodendroglial hyperplasia in epilepsy using single-nucleus multiomics - Galvão, Isabella C.; Lemoine, Manuela; Kandratavicius, Ludmyla; Yasuda, Clarissa L.; Alvim, Marina K.M.; Ghizoni, Enrico; Blümcke, Ingmar; Cendes, Fernando; Rogerio, Fabio; Lopes-Cendes, Iscia; Veiga, Diogo F.T. (Epilepsia, 2025)
Objective: Mild malformations of cortical development with oligodendroglial hyperplasia in epilepsy (MOGHE) are brain lesions associated with focal epilepsy and characterized by increased oligodendroglial density, heterotopic neurons, and hypomyelination in the white matter. Although previous studies have implicated somatic mutations in the SLC35A2 gene, the cellular and molecular mechanisms underlying MOGHE pathogenesis remain elusive. To address this gap, this study aimed to systematically characterize the cell type composition and molecular alterations of MOGHE lesions at cellular resolution using single-nucleus multiomic profiling. Methods: We performed single-nucleus multiomic sequencing to obtain paired gene expression and chromatin accessibility profiles of >31 000 nuclei from gray matter and white matter regions of MOGHE lesions and compared the results with publicly available neurotypical control datasets. Results: The analysis of gray and white matter regions from two MOGHE patients revealed significant cellular composition alterations, including the presence of heterotopic neurons and disease-specific oligodendrocyte populations within the subcortical white matter. MOGHE-specific oligodendrocytes were characterized by the upregulation of synaptic functions and enhanced neuron communication, denoting a possible role in synaptic support and the mediation of glia–neuron interactions in the disease. On the other hand, MOGHE heterotopic neurons were characterized by the upregulation of genes associated with neuronal migration and the Wnt signaling pathway, suggesting a mechanism underlying their atypical localization. Significance: This high-resolution cell type mapping of MOGHE lesions in clinical samples unveils neuronal and glial populations affected by the disease and provides novel insights into the pathophysiological mechanisms of MOGHE.
CRIS-Team Scopus Importer:2025-05-16
Keywords: epilepsy; gene expression; malformations of cortical development; MOGHE; oligodendrocytes; single-nucleus ATAC sequencing; single-nucleus RNA sequencing